Plan de exportación de limón Tahití en fresco desde el municipio de Miraflores- Boyacá con la empresa Asofrumir hacia Miami Estados Unidos (2023)
this study analyzes the Colombian fruit and vegetable sector based on the production of Tahiti lemon, as it is one of the products with the greatest export potential in the country, non-traditional raw materials are in the process of transformation, and the use of the geographic potential of the territory Colombian also manifests itself as a competitive advantage in the production of tropical fruits.